On-off characteristics of luminosity fluctuations of pulsating auroras - Yamamoto, Tatsundo (1983)
P(論文) Characteristics of on-off switchings in luminosity of a single point within the pulsating auroral displays were studied on typical three examples. The most striking feature in luminosity fluctuations is the remarkable consistency in pulsation "on" intervals in comparison with "off" intervals. Amplitude maxima in each pulsation cycle were fairly constant throughout a continuous train of pulses. No relationships were found between "on" and "off" intervals. These observations suggest that the pulsation "on" interval is the essential time constant of the phenomena, and the luminosity fluctuations of pulsating auroras consist of individual isolated pulses. departmental bulletin paper